R&D policy instruments – a critical review of what we do and don't know. Issue 2 (17th February 2016) - Martin, Ben R.
Abstract: In recent years, the term "policy instrument" has been used frequently with regard to R&D policy and innovation policy. This article examines the development of the term as part of a body of research known as "policy design". Over the last 50 years, there has been substantial progress in setting policy design on a more systematic basis, with the development of established concepts and analytical frameworks, including various taxonomies of policy instruments. However, with just a few exceptions, this body of research seems to have had little impact in the world of R&D policy. The paper reviews the literature on R&D policy instruments, identifies a number of challenges for R&D policy instruments in the light of four transitions and sets out a research agenda for the study of R&D policy instruments, before ending with a number of conclusions.